2000
DOI: 10.1177/00220345000790031101
|View full text |Cite
|
Sign up to set email alerts
|

AgNOR are Sensitive Markers of Radiation Lesions in Squamous Epithelia

Abstract: The possibility of detection of incipient cellular alterations is central to early diagnosis and to clinician's capacity to discriminate between samples that appear similar on routine preparations. We examined the value of silver-stained nucleolar organizer regions (AgNOR) in detecting radio-induced alterations in a model of squamous epithelium biologically similar to oral mucosa. Morphometry of AgNOR has been proven to be of value in the detection of incipient cellular alterations. This method allows for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This is because the criteria for AgNOR count in histological sections differ from the criteria for cytological smears. 20 Although, many studies have performed AgNOR count in oral mucosa with benign, premalignant, and malignant tumors (a few of which were found in those exposed to tobacco smoking and alcohol), we didnot find any study that has assessed normal oral mucosa exposed to peppers or hot food and drink consumption. Most previous studies that have assessed oral mucosal lesions by AgNOR focused solely on the AgNOR count, and very few studies have added keratinization of the oral mucosal cells besides AgNOR counts.…”
Section: Discussionmentioning
confidence: 90%
“…This is because the criteria for AgNOR count in histological sections differ from the criteria for cytological smears. 20 Although, many studies have performed AgNOR count in oral mucosa with benign, premalignant, and malignant tumors (a few of which were found in those exposed to tobacco smoking and alcohol), we didnot find any study that has assessed normal oral mucosa exposed to peppers or hot food and drink consumption. Most previous studies that have assessed oral mucosal lesions by AgNOR focused solely on the AgNOR count, and very few studies have added keratinization of the oral mucosal cells besides AgNOR counts.…”
Section: Discussionmentioning
confidence: 90%
“…Silver stainable nucleolar organizer regions (AgNORs) have been shown to be replicatory markers (5). Studies suggest potential usefulness of AgNOR parameters, such as mean count and area of distribution within the nucleus, in diagnosis and prognosis of various neoplasms (5–11), especially oral squamous cell carcinoma (6, 9, 12, 13). Mean AgNOR counts can be useful in diagnosing histological features representing oral leukoplakia (6) and have been shown to correlate with clinical outcomes of various cancers (12, 14–16).…”
mentioning
confidence: 99%
“…Silver stainable nucleolar organizer regions (AgNORs) have been shown to be replicatory markers and many studies have shown the potential usefulness of AgNOR parameters like mean count area of distribution in the nucleus in diagnosis of various neoplasms (5–10). Oral squamous cell carcinoma can be distinguished from normal epithelium by AgNOR count (5, 8, 11, 12).…”
mentioning
confidence: 99%